2019
DOI: 10.1042/bcj20190289
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures of Magnaporthe oryzae trehalose-6-phosphate synthase (MoTps1) suggest a model for catalytic process of Tps1

Abstract: Trehalose-6-phosphate (T6P) synthase (Tps1) catalyzes the formation of T6P from UDP-glucose (UDPG) (or GDPG, etc.) and glucose-6-phosphate (G6P), and structural basis of this process has not been well studied. MoTps1 (Magnaporthe oryzae Tps1) plays a critical role in carbon and nitrogen metabolism, but its structural information is unknown. Here we present the crystal structures of MoTps1 apo, binary (with UDPG) and ternary (with UDPG/G6P or UDP/T6P) complexes. MoTps1 consists of two modified Rossmann-fold dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 25 publications
2
13
0
Order By: Relevance
“…Both lobes are spanned by an α-helix, formed by residues 572-603 (Figure 2D). Each domain contains a modified Rossman fold that is characteristic of the retaining glycosyltransferase family (40, 51) (Figure 2D), and similar to the published CaTps1 and CaTps1-like N-terminal domain of CaTps2 structures (Supplemental Figure 5) (34,41,43). A common feature that is observed in these substrate-free structures is a lack of density in portions of the N-terminus, suggestive of conformational flexibility in the absence of ligands.…”
Section: Trehalose Biosynthesis Protein Cntps1 Self-associates In Bac...supporting
confidence: 68%
See 1 more Smart Citation
“…Both lobes are spanned by an α-helix, formed by residues 572-603 (Figure 2D). Each domain contains a modified Rossman fold that is characteristic of the retaining glycosyltransferase family (40, 51) (Figure 2D), and similar to the published CaTps1 and CaTps1-like N-terminal domain of CaTps2 structures (Supplemental Figure 5) (34,41,43). A common feature that is observed in these substrate-free structures is a lack of density in portions of the N-terminus, suggestive of conformational flexibility in the absence of ligands.…”
Section: Trehalose Biosynthesis Protein Cntps1 Self-associates In Bac...supporting
confidence: 68%
“…Inspection of the Tps1 crystal structures from Candida albicans (40), Aspergillus fumigatus (40), E. coli (37, 38), Streptomyces venezuelae (34) and Magnaporthe oryzae (43) and the catalytically inactive Tps1-like N-terminal domain of C. albicans Tps2 (41) revealed that Tps1 most likely exists as a homo-tetramer. To determine if subunits of the Cryptococcus neoformans var.…”
Section: Resultsmentioning
confidence: 99%
“…7A). The template used was the trehalose-6-phosphate synthase (PDB 6JBR) from Pyricularia oryzae (Wang et al 2019). The identity and coverage of both proteins were 32.66 and 77% respectively.…”
Section: Molecular Modeling Of Putative Proteins Involved In Abiotic ...mentioning
confidence: 99%
“…In particular, the latter is an essential step for the penetration of M. oryzae into host plants. Also, the synthesis of melanin is critically dependent on the activity of an enzymatic superfamily called glycosyltransferase, especially trehalose-6-phosphate synthase [7].…”
Section: Introductionmentioning
confidence: 99%